Motivations for swiss lowland farmers to conserve biodiversity: Identifying factors to predict proportions of implemented ecological compensation areas. (August 2018) - Gabel, Vanessa M.; Home, Robert; Stolze, Matthias; Pfiffner, Lukas; Birrer, Simon; Köpke, Ulrich
Highlights: There is a relationship between beliefs, motivations and implemented ECA on farms. There are differences between beliefs of organic farmers non-organic farmers. Financial incentives are independent from beliefs.